External influences and local responses. Changes in Polish higher education 1990-2005 (CPP RPS 27/2011) - Antonowicz, Dominik (Center for Public Policy Research Papers Series, 2011)
During the last two decades, higher education in Poland has undergone substantial changes. This study focuses specifically on the timeframe 1990-2005, as this was a period in which the higher education system in Poland was heavily impacted by external influences. This timeframe is marked by two major events - approval of the Laws on Higher Education by the Polish Parliament, first in 1990 and last in 2005. The years between 1990 and 2005 saw the Polish higher education system experiencing a struggle between an expectation to adopt Western European model(s) of governance (analogical to the economy and political system) and the aspirations of the academic community to restore the mythical concept of the university as the ivory tower.